Numerical reactive diffusion modeling of stacked elemental layer rapid thermal annealed chalcopyrite absorber layer formation - Zweschke, André; Wellmann, Peter (Thin Solid Films, 2015)
The diffusion processes during chalcopyrite (CuInSe) layer formation by rapid thermal annealing (RTA) of stacked elemental layers are still not completely understood. We present a one-dimensional kinetic model, which describes the diffusive reaction kinetics for layers of partial miscible systems to describe the RTA process. The model was applied to a layer stack of elemental Se between the metallic layers Cu and In. First, some binary phases occur. After the Se layer is consumed, CuInSeis observed between the binary compounds CuSe and InSe.
Keywords: Chalcopyrite; Reactive diffusion; Diffusion modeling